2007
DOI: 10.1152/physiolgenomics.00057.2006
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture suppresses myostatin gene expression: cell proliferative reaction in mouse skeletal muscle

Abstract: Complementary and alternative medicine (CAM) may provide patients with an alternative to traditional medicine, but an assessment of its efficacy is required. One CAM method, electroacupuncture (EA) treatment, is a maneuver that utilizes stimulation of acupuncture needles with a low-frequency microcurrent. To study the effect of short-term EA, we evaluated the differential expression of genes induced by EA in mouse skeletal muscle for up to 24 h. We then used RT-PCR to confirm the expression patterns of six dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 53 publications
(60 reference statements)
2
45
0
1
Order By: Relevance
“…16 Electrical acupuncture treatment has been shown to suppress myostatin expression, which leads to a satellite cell-related proliferative reaction and repair in skeletal muscle. 17 Low-frequency electrical stimulation (LFES) is an acupuncture technique that replicates the benefits of resistance exercise through stimulation of muscle contraction.…”
mentioning
confidence: 99%
“…16 Electrical acupuncture treatment has been shown to suppress myostatin expression, which leads to a satellite cell-related proliferative reaction and repair in skeletal muscle. 17 Low-frequency electrical stimulation (LFES) is an acupuncture technique that replicates the benefits of resistance exercise through stimulation of muscle contraction.…”
mentioning
confidence: 99%
“…4), an endogenous inhibitor of muscle growth and satellite cell-related muscle regeneration, and EA induced a proliferative reaction of muscle satellite cells (Fig. 4) (Takaoka et al, 2007). Thus, in view of our previous basic research, EA may be an effective method for retaining muscle mass.…”
Section: Fig 1 Schematic Diagram Of Transmission Of Electroacupunctmentioning
confidence: 78%
“…Electroacupuncture (EA) is a modified acupuncture technique that utilizes electrical stimulation. Previous studies have demonstrated that EA has therapeutic effects on chondral defects including knee osteoarthritis (10)(11)(12) and produces cytokines with multiple biological activities in various types of diseases (13)(14)(15). In addition, animal experiments have shown that EA enhances BMSC differentiation into neuronal cells (16).…”
Section: Introductionmentioning
confidence: 99%